Two-Dimensional Image of Seismic Refraction Tomography and Electrical Resistivity Tomography Survey in a Geophysical Proposed Test Site at Shika, Ahmadu Bello University Nigeria (Global Journal of Science Frontier Research, 2019)
Due to the growing and advancement in technology being applied in geophysics, it is of importance that a geophysical test site center be established for calibration, training and demonstration of such equipment. An integrated geophysical survey of the area was carried out with the aim of characterizing the subsurface structures and lithology of the area. Thereafter, different types of objects that respond to all geophysical techniques will be buried at different depths in the site. Seismic refraction and electrical resistivity tomography was used, using both the seistronix RAS 24 seismograph and SAS 4000 ABEM Terameter equipment. A total of five profiles were taken at a total length of 300 m and an inter-profile spacing of 45 m. The results of this survey in correlation with borehole data revealed three distinct layers; overburden, weathered basement and fresh basement. The overburden consist of the top soil and lateritic clay, averaging a depth of 3-6 m and having a seismic velocity of 85 m/s -300 m/s. Underneath the overburden is the weathered basement, consisting of brownish fine to medium grained coarse sand, gravel and some disintegrated schistose material, having a seismic velocity of 583 m/s -4834 m/s. The depth to the third layer (fresh basement) suggested less compact subsurface, a close examination of the velocities with depth shows higher velocities at deeper depths.
Keywords: Seistronix RAS 24 seismograph and SAS 4000 ABEM Terameter equipment